Predictive factors for pancreatitis and cholecystitis in endoscopic covered metal stenting for distal malignant biliary obstruction. Issue 1 (19th December 2012) - Shimizu, Shuya; Naitoh, Itaru; Nakazawa, Takahiro; Hayashi, Kazuki; Miyabe, Katsuyuki; Kondo, Hiromu; Yoshida, Michihiro; Yamashita, Hiroaki; Umemura, Shuichiro; Hori, Yasuki; Ohara, Hirotaka; Joh, Takashi
Abstract Background and Aim Pancreatitis and cholecystitis are major complications after self‐expandable metal stent (SEMS) placement in distal malignant biliary obstruction. We aimed to clarify predictive factors for pancreatitis and cholecystitis after covered SEMS placement. Methods We retrospectively reviewed 74 consecutive patients with distal malignant biliary obstruction who underwent initial endoscopic drainage using covered SEMS. Predictive factors for pancreatitis and cholecystitis were evaluated in the 74 patients described above and in 66 patients who had not undergone cholecystectomy. Results The incidences of pancreatitis and cholecystitis were 10.8% (8/74) and 6.1% (4/66), respectively. Univariate analysis revealed that non‐pancreatic cancer (P = 0.018) and contrast injection into the pancreatic duct (P = 0.030) were significant predictive factors for pancreatitis. Multivariate analysis revealed that non‐pancreatic cancer (odds ratio [OR], 4.21; 95% confidence interval [CI], 1.63–14.18; P = 0.007) and contrast injection into the pancreatic duct (OR, 3.34; 95% CI, 1.33–9.60; P = 0.016) were significant independent predictive factors for pancreatitis. On the other hand, univariate and multivariate analyses revealed that tumor involvement to the orifice of the cystic duct (OCD) was a significant independent predictive factor for cholecystitis (OR, 5.85; 95% CI, 1.91–27.74; P = 0.005). Conclusions Non‐pancreatic cancer and contrast injection into the pancreatic duct were predictive factors for pancreatitis, and tumor involvement to the OCD was a positive predictive factor for cholecystitis after endoscopic covered SEMS placement for distal malignant biliary obstruction.